MicroRNA-155, -185 and -193b as biomarkers in human papillomavirus positive and negative tonsillar and base of tongue squamous cell carcinoma. (July 2018) - Bersani, Cinzia; Mints, Michael; Tertipis, Nikolaos; Haeggblom, Linnea; Näsman, Anders; Romanitan, Mircea; Dalianis, Tina; Ramqvist, Torbjörn
Highlights: miR-155 expression is related to presence of HPV, T-stage, CD8 + TIL counts and outcome. miR-185 expression is related to presence of HPV and tends to be related to survival. miR-193b expression is related to T-stage, patient gender and CD8 + TIL counts. miR-155 and miR-185 can be combined to predict patient survival in HPV + cancer. Abstract: Objective: Three-year disease-free survival (DFS) is 80% for human papillomavirus (HPV) positive tonsillar and base of tongue cancer (TSCC/BOTSCC) treated with radiotherapy alone, and today's intensified therapy does not improve prognosis. More markers are therefore needed to more accurately identify patients with good prognosis or in need of alternative therapy. Here, microRNAs (miRs) 155, 185 and 193b were examined as potential prognostic markers in TSCC/BOTSCC. Material and methods: 168 TSCC/BOTSCC patients diagnosed 2000–2013, with known data on HPV-status, CD8 + tumour infiltrating lymphocytes, tumour staging and survival were examined for expression of miR-155, -185 and -193b using Real-Time PCR. Associations between miR expression and patient and tumour characteristics were analysed using univariate testing and multivariate regression. Results: Tumours compared to normal tonsils showed decreased miR-155 and increased miR-193b expression. miR-155 expression was associated with HPV-positivity, low T-stage, high CD8 + TIL counts and improved survival. miR-185 expression was associated with HPV-negativity and a tendency towards decreased survival, while miR-193b expression was associated with higher T-stage, male gender and lower CD8 + TIL counts, but not with outcome. Upon Cox regression, miR-185 was the only miR significantly associated with survival. Combining miR-155 and miR-185 to predict outcome in HPV + patients yielded an area under curve (AUC) of 71%. Conclusion: Increased miR-155 expression was found as a positive predictor of survival, with the effect mainly due to its association with high CD8 + TIL numbers, while miR-185 independently associated with decreased survival. Addition of these miRs to previously validated prognostic biomarkers could improve patient stratification accuracy.